The Internalization of Ahl al-Sunnah wa al-Jamā‘ah al-Nahdliyah Islamic Values through Quarterly Routine Activities in South Sumatra, Indonesia - Mutia Kamil; Irhamudin Irhamudin; Abrori, M. Sayyidul (KURAS Institute, 2025)
This study examines the process of internalizing the Islamic values of Ahl al-Sunnah wa al-Jamā‘ah (Aswaja) Al-Nahḍiyyah through quarterly religious activities in Sungai Sibur Village, South Sumatra, Indonesia. Sungai Sibur represents a rural community that continues to preserve locally embedded Islamic traditions rooted in Aswaja principles. A descriptive qualitative approach was employed, involving religious leaders and representatives of the Muslimat NU congregation as research participants. Data were collected through observation, in-depth interviews, and documentation, and were analyzed thematically. The findings reveal that the quarterly activities engage diverse segments of the community, including Muslimat NU members and local religious figures. These activities serve as an effective mechanism for internalizing Aswaja values particularly moderation (tawassuṭ), balance (tawāzun), and tolerance (tasāmuḥ). The internalization process occurs through habituation, exemplary practices, social interaction, and contextually relevant religious understanding. Moreover, the activities contribute to strengthening Nahdlatul Ulama identity, fostering Islamic social cohesion (ukhuwah Islamiyah), and shaping the community’s religious character. Nevertheless, challenges remain, notably limited religious literacy among certain community members and geographical constraints. This study underscores the significant role of local religious traditions in promoting moderate and religious character formation within rural Muslim communities.